Benson And Guided Imagery Combination In Gastritis Pain Reduction: Kombinasi Terapi Benson Dan Guided Imagery Pada Nyeri Gastritis - Khasanah, Tia Meilana Uswatun; Sukarmin, Sukarmin; Siswanti, Heny (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Gastritis is a common gastrointestinal disorder frequently accompanied by epigastric pain that interferes with patient comfort and daily functioning. Specific Background: Non-pharmacological nursing interventions such as Benson relaxation therapy and guided imagery have been individually applied to manage pain in gastritis patients, particularly in primary healthcare settings. Knowledge Gap: However, empirical evidence examining the combined application of Benson therapy and guided imagery as a structured intervention in community health centers remains limited. Aims: This study aimed to examine the outcomes of a combined Benson therapy and guided imagery intervention on pain levels among gastritis patients at a primary healthcare center. Results: Using a quasi-experimental pretest–posttest control group design with 32 participants, the intervention group demonstrated a marked shift from moderate–severe pain to predominantly mild pain after the intervention, while the control group receiving pain management education showed a smaller reduction. Statistical analysis indicated significant pre–post differences within the intervention group and significant differences between groups after intervention. Novelty: The novelty of this study lies in the standardized combination of Benson relaxation and guided imagery implemented as a single nursing intervention package in a primary care context. Implications: These findings support the integration of combined Benson therapy and guided imagery into routine nursing care as a feasible, safe, and low-cost non-pharmacological approach for managing gastritis-related pain in primary healthcare services. Highlights • Demonstrated pain level shift toward mild categories following combined relaxation intervention• Showed significant differences between intervention and education-only groups• Supported structured non-pharmacological nursing care in primary health centers Keywords Benson Therapy; Guided Imagery; Gastritis Pain; Non Pharmacological Nursing; Primary Health Care